(3GdhGVM aj GdQei HGdfTGHIs - (3YHO GdQMef Hf CMeO GdWHQjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf EbQGQkG HQHhHjJg gPG cJGH CdaJGg ai GdQei HGdfTGHI GdWhjdI hGdbUjQI s
(3BNQgG (B:s
(3hgj JYed ef GdOQhY hJYed GeJdGA GdMSHGfg Ohf SYI GdeLQi hcjdG hHGddg GdJhajb s
(3QHeG jchf GdeDda CHh LYaQ eMeO Hf LQjQ GdWHQis
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(2 / 32 (3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs